Phytochemicals from Bangladeshi Medicinal Plants Potentially Targeting Non-Structural Protein 2/Non-Structural Protein 3 Chimera of Dengue Virus: An in silico study - Morshed, Niaz; Reza, Rumman; Samdani, Md Nazmus; Asaduzzaman, Muhammad (Dhaka University Journal of Pharmaceutical Sciences, 2022)
In Bangladesh, the incidence and death rate of patients suffering from dengue infection are escalating. To date, there is no effective antiviral against dengue virus. Treatment regimen mostly includes symptomatic management of the disease. In this study, we performed molecular docking with 36 phytochemicals extracted from Bangladeshi medicinal plants namely Averrhoa carambola L., Curcuma longa L., Nyctanthes arbor-tristis L. and Zingiber officinale against dengue virus non-structural protein 2/non-structural protein 3 (NS2/NS3) chimera. The NS2/NS3 complex functions simultaneously as helicase/protease and/or RNA-tri-phosphatase. The compounds calceolarioside A, ᵞ-elemene, β-sitosterol, β-elemene and curcuminoid-D exhibited high binding affinity (ranging from -8.3 to -7.2 kJ/mol) towards the selected protein and their drug-likeness was confirmed via ADMET analysis. Hence, these compounds have the potential to inhibit viral replication as indicated by computational calculation. However, further in vitro and in vivo studies can be undertaken to confirm such inhibitory properties of the reported phytochemicals. Dhaka Univ. J. Pharm. Sci. 20(3): 417-426, 2022 (June) Centennial Special Issue